Global patterns in soil seed bank seasonality: a meta-analysis of ecosystem and functional group dynamics - Peng, Li; Shi, Yafei; Lin, Dong; Niu, Furong; Liu, Xiaoni; Wang, Yuzhen (Frontiers in Plant Science, 2025)
IntroductionSoil seed banks are key components driving vegetation dynamics and maintaining ecosystem resilience, and their composition and abundance play crucial roles in the establishment, maintenance, and regeneration of plant communities. Although previous studies have documented seasonal variation in soil seed banks, most have been limited to local or regional scales.MethodsTo address this gap, we conducted a global meta-analysis based on 1,018 paired observations from diverse regions to systematically assess changes in soil seed bank density and species richness across early, mid, and late growing seasons.ResultsOur results show that soil seed banks exhibit seasonal variation at the global scale, with patterns differing among ecosystem types and plant functional groups, and some differences reaching statistical significance. Specifically, annuals and legumes had higher seed bank densities in the late season compared to the mid-season. Grassland ecosystems showed the most pronounced seasonal fluctuations, with mid-season densities significantly lower than in the early and late growing seasons. In addition, transient seed banks supported significantly higher species richness than persistent seed banks.ConclusionThese findings reveal the seasonal dynamics of soil seed banks at the global scale and demonstrate how ecosystem types and plant functional groups influence these patterns. Overall, this study provides new insights into plant community succession and ecosystem management.